Effect of Nacl on Germination and Seedling Growth of Some Cotton Genotypes (Research in Agriculture Livestock and Fisheries, 2020)
Salinity is an emerging problem among the abiotic stresses of plants in Bangladesh. One easy way to cope with the problem of salinity is to exploit the genetic potential of plants for their adaptability to adverse soil conditions. Salt tolerance improvement might be achieved through selection from already existing germplasm which can be done by quick method particularly in early growth stages of crops. A laboratory experiment was conducted to determine the effect of salinity on germination and the seedling growth of five cotton genotypes. Two factors include genotypes (CB-9, CB-10, CB-12, CB-14 and CB-15) and salt solution of different concentrations (control -0 dS m-1, 4 dS m-1, 8 dS m-1, 12 dS m-1 and 16 dS m-1) were used. Relative to control treatment, germination energy and germination capacity at 16 dS m-1 was maximum in CB-12 (0.72 and 0.77 respectively) whereas germination percentage (0.99) was maximum in CB-9 and the relative value of all the above parameters was minimum in CB-15 (0.02, 0.13, 0.41 and 0.09, respectively). In case of seedling growth parameters, shoot length, seedling vigor index and dry weight at 16 dS m-1 were maximum in CB-9 (0.67, 0.64 and 0.77 respectively) relative to control whereas the relative value of all those parameters was minimum in CB-15 (0.5, 0.17, 0.31 and 0.59 respectively). Considering all germination and seedling growth parameters, CB-9 was supposed to be superior genotype followed by CB-12, CB-10 and CB-14 whereas genotype CB-15 was more susceptible than other genotypes against salinity stress.Res. Agric., Livest. Fish.7(2): 199-207,  August 2020